EDUKASI PERAWATAN PAYUDARA TERHADAP PENINGKATAN PENGETAHUAN PADA IBU HAMIL PRIMIGRAVIDA DALAM MENYUSUI - Sibua, Siska N.; Patonengan, Gita Sandy; Dilly, Alya Nurhasanah (Lasalle Health Journal, 2026)
Introduction: Breast care during pregnancy is vital for preparing for future breastfeeding. To ensure the breasts function optimally once the baby is born, breast care should be planned throughout the pregnancy. A lack of awareness among pregnant women regarding breast care can impact milk production and the behavior of providing exclusive breastfeeding for the first six months. Many pregnant women do not perform breast care due to a lack of understanding of the necessary information. Objective: To analyze the impact of Breast Care Education on the knowledge improvement of primigravida pregnant women regarding breastfeeding at the Public Health Center (UPTD). Methods: This study utilized a one-group pre-test and post-test design with a quantitative quasi-experimental method. The sampling technique used was total sampling, involving the entire population as the research sample; thus, the total population of 15 pregnant women was included. Results: There is an influence of breast care education on the increase of knowledge among pregnant women. This is evidenced by the results of the Wilcoxon Signed-Rank Test, which showed a p-value = 0.001. Conclusion: It is expected that the Motoboi Kecil Public Health Center (UPTD) will establish breast care education as a routine program within antenatal services. Health workers should provide consistent counseling so that pregnant women, particularly primigravidas, are encouraged to actively participate and independently practice the breast care techniques taught.